Physicochemical And Rheological Properties Of Fish Gelatin Modified By Tannic Acid - Amir, Sazereen (Universiti Sains Malaysia, 2021)
Fish gelatin was gaining attention as an alternative gelatin because mammalian gelatin faced social cultural issue and also health concern. However, fish gelatin has poor physicochemical and rheological properties. Therefore, the purpose of this study was to investigate the physicochemical and rheological properties of fish gelatin treated with tannic acid at different concentration which is 0%, 2%, 4% and 6%. The physicochemical and rheological properties such as colour, viscosity, gel strength, flow and viscoelastic properties of gelatin was observed. Colour measurement shows that there was decrease in lightness and increase in redness and yellowness of fish gelatin as the concentration of tannic acid increase that was treated with tannic acid because fish gelatin turned from pale yellow to dark brown due to tannic acid oxidation. FTIR analysis revealed increment in amide band region in treated fish gelatin indicating that oxidized tannic acid interacts with gelatin by covalent bonding with the amino group in gelatin.